Pengaruh Advertising Terhadap Keputusan Tamu Untuk Menginap Di Aston Bogor Hotel And Resort - Avian Sapulette; Elisdha Theresia Simanjuntak; Fauzia Tutupoho; Harold Hursepuny (Jurnal Administrasi Terapan, 2024)
Marketing is the management process responsible for identifying, anticipating and satisfying customer requirements profitably. Successful marketing communication relies on a combination of options called the promotional mix. These options include advertising, sales promotion, public relations, direct marketing, and personal selling. Advertising is utilized primarily to attract new guests and serves to build awareness. Advertising is far more specific than marketing; advertising is a function of marketing, and basically encompasses methods of communication with audience designed to produce sales enquiries, and/or improve awareness/perceptions of product/brand/organization. Advertising refers to printed and electronic media that is presented one way or another to market or audience, including packaging, point of sale, brochures and sales literature. Advertising (when properly executed) is the statistically driven and measurable implementation of marketing strategy, via carefully selected communications methods, targeted at predetermined audiences.When all the company’s departments work together to serve the customer’s interests, theresult is integrated marketing. The analytical tools used in the project were: 1) technique statistical analysis Pearson Product Moment Correlation. 2) Statistics coefficient determinant. 3) hypotesis test. The results of calculating the product moment correlation by 0,66 and the coefficient of determinant by 43,56% and according to the t test of the calculation by 14,09 and 2,0 t test table which shows that t calculate > t tabel or 14,09 > 2,0 which means that the hypotesis Ho is rejected and Ha is accepted where there is a significant correlation between the advertising to the guest make decision in choosing Aston Bogor Hotel and Resort. Keywords : Promotion, Advertising, Decision guests, Aston Bogor Hotel and Resort